(untitled) (New York, 2007)
This collection of exclusive articles presents the latest research in the area of mergers and acquisitions. It presents what drives corporate performance under different economic conditions, both in the US and across the globe, and examines the role of mergers and acquisitions in maintaining the efficiency of world markets.
Sáp nhập và mua lại công ty
Keywords: Consolidation and merger of corporations.,Sự liên kết và thống nhất của các tập đoàn